A longitudinal pilot study in pre-menopausal women links cervicovaginal microbiome to CIN3 progression and recovery - Cristiana Banila; Efthymios Ladoukakis; Dorota Scibior-Bentkowska; Leandro Rodrigues Santiago; Caroline Reuter; Michelle Kleeman; Belinda Nedjai (Communications Biology)
Abstract Increasing evidence suggests vaginal dysbiosis is associated with persistent high-risk human papillomavirus (hrHPV) infection and cervical intraepithelial neoplasia (CIN) development. In this pilot longitudinal study, we investigate the potential of vaginal microbiome biomarkers to predict CIN3 development in hrHPV-positive (hrHPV+) women of reproductive age and assess loop electrosurgical excision procedure (LEEP) outcomes. Fifty-nine non-menopausal women 20–53 years old, with normal cytology, were selected from the ARTISTIC trial and followed up twice over six years. Vaginal microbiome was analysed by 16S rRNA sequencing. HrHPV+ women with CIN3 showed a significant overrepresentation of Sneathia amnii, Megasphaera genomosp., Peptostreptococcus anaerobius and Achromobacter spanius (p < 0.05). Successfully LEEP-treated hrHPV-negative women exhibited increased Lactobacillus species, especially Lactobacillus gasseri. Additionally, Lactobacillus helveticus, suntoryeus and vaginalis showed a potential protective role against CIN3 development. These unique microbial biomarkers associated with CIN3 development and recovery following LEEP treatment bring new insights into the vaginal microbiome’s role on disease progression.